Campur Kode dalam Dialog Film Milly & Mamet: Kajian Sosiolinguistik: Code-Mixing in the Dialogues of Film Milly & Mamet: A Sociolinguistic Analysis - Siburian, Elsa; Widayati, Dwi; Nasution, Latifah Yusri (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
The purpose of this study is to describe the types and factors that cause code-mixing, using qualitative descriptive research methods and the matching method. Data collection techniques included listening, recording, and note-taking, while data analysis was conducted using the Determinant Element Sorting technique. The theories applied included sociolinguistics, bilingualism, and multilingualism, as well as the concept of code-mixing according to Muysken and Suwito. The results of the study show that the film’s dialogue contains three types of code-mixing: insertion, alternation, and congruent lexicalization, with insertion being the most prevalent. Examples of insertion include base words, affixed words, and compound words. Alternation involves switching from Indonesian to English and from Sundanese to Indonesian. Congruent lexicalization encompasses foreign and mixed lexical items. The use of code-mixing is also influenced by factors such as role identification, variety identification, and the desire to explain and interpret. Thus, the use of code-mixing in the film’s dialogue reflects the speakers’ adaptation to their roles, the context, and their communicative needs.